Association of Depression With Past-Month Cannabis Use Among US Adults Aged 20 to 59 Years, 2005 to 2016 - Gorfinkel, Lauren R. (JAMA Netw Open, 2020)
IMPORTANCE: Despite studies showing that repeated cannabis use may worsen depressive symptoms, the popular media increasingly presents cannabis as beneficial to mental health, and many members of the public view cannabis as beneficial for depression. Therefore, cannabis use among individuals with depression may be becoming more prevalent. OBJECTIVE: To examine the association of depression with past-month cannabis use among US adults and the time trends for this association from 2005 to 2016. DESIGN, SETTING, AND PARTICIPANTS: This repeated cross-sectional study used data from 16 216 adults aged 20 to 59 years who were surveyed by the National Health and Nutrition Examination Survey, a national, annual, cross-sectional survey in the United States, between 2005 and 2016. Data analysis was conducted from January to February 2020. EXPOSURES: Survey year and depression, as indicated by a score of at least 10 on the Patient Health Questionnaire–9. MAIN OUTCOMES AND MEASURES: Any past-month cannabis use (ie, ≥1 use in the past 30 days) and daily or near-daily past-month cannabis use (ie, ≥20 uses in the past 30 days). Logistic regression was used to examine time trends in the prevalence of cannabis use, depression, and the association between cannabis use and depression from 2005 to 2016. RESULTS: The final analysis included 16 216 adults, of whom 7768 (weighted percentage, 48.9%) were men, 6809 (weighted percentage, 66.4%) were non-Hispanic White participants, and 9494 (weighted percentage, 65.6%) had at least some college education. They had a weighted mean age of 39.12 (95% CI, 38.23-39.40) years. Individuals with depression had 1.90 (95% CI, 1.62-2.24) times the odds of any past-month cannabis use and 2.29 (95% CI, 1.80-2.92) times the odds of daily or near-daily cannabis use compared with those without depression. The association between cannabis use and depression increased significantly from 2005 to 2016. The odds ratio for depression and any past-month cannabis use increased from 1.46 (95% CI, 1.07-1.99) in 2005 to 2006 to 2.30 (95% CI, 1.82-2.91) in 2015 to 2016. The odds ratio for depression and daily or near-daily past-month cannabis use increased from 1.37 (95% CI, 0.81-2.32) in 2005 to 2006 to 3.16 (95% CI, 2.23-4.48) in 2015 to 2016. CONCLUSIONS AND RELEVANCE: The findings of this study indicate that individuals with depression are at increasing risk of cannabis use, with a particularly strong increase in daily or near-daily cannabis use. Clinicians should be aware of these trends and the evidence that cannabis does not treat depression effectively when discussing cannabis use with patients.